STUDY REGARDING THE USE OF MULTIMEDIA TECHNOLOGIES IN TOURISM SECTOR OF SUCEAVA COUNTY - Iulian CONDRATOV (Revista de Turism: Studii si Cercetari in Turism, 2012)
Through the study presented in this paper we wanted to point out some aspects that characterize the behavior of the administrators of tourist unities on the territory of Suceava county regarding the use of internet as an information and promotion instrument. The research objectives followed: the determination of the way in which the agents from the tourism sector regard the promotion activity; the determination of the way in which the companies from the tourism sector build their promotion strategy; the identification of the degree of the use of web environment within the promotion strategy; the determination of the degree in which the period of functionality and the setting category of the tourism structure influence the decision of using the web instruments in view of promotion; the identification of the degree in which the tourism agents are available to offer a technical support in order that an online application of tourism recommendation can be used from the inside of the tourism unity.